The Influence of Climatic Aging on the Performance of Wood-Based Panels - Ekaterina Pakhomova; Sergey Emelyanov; Viktor Yartsev; Vladislav Danilov; Pavel Monastyrev (Salehan Institute of Higher Education, 2023)
The purpose of this work is to experimentally determine the climatic effects on the performance of wood-based panels using the methodology developed on the basis of the thermo-fluctuation concept of material aging. This methodology makes it possible to determine the durability of the material by taking into account the simultaneous action of temperature, time, and mechanical stress, as well as additional external influences. The experiments were conducted on particleboard, fiberboard, and plywood. The following climatic effects were studied experimentally in specialized laboratory facilities: high humidity, thermal aging, and UV-irradiation. As the evaluation indicators of the performance characteristics of wood boards were selected, water absorption, swelling rate, thermal expansion, penetration strength, and bending strength. From a theoretical point of view, the value of this work lies in demonstrating a methodology for determining the performance characteristics of particleboard, fiberboard, and plywood, which is highly accurate by considering these characteristics together rather than separately. From a practical point of view, this paper contains experimental results that allow us to judge the characteristics of the wood boards. It has been proven that exposure to UV rays and heat aging causes the binder between the filler particles to break down, and moisture is detrimental to the filler. The thermo-fluctuational constants obtained in the course of the study make it possible to predict the durability of the materials in question over a large range of operating parameters. Doi: 10.28991/CEJ-2023-09-06-015 Full Text: PDF